The influence of protein levels on body weight, body dimensions, and reproductive characteristics of local chickens treated in-ovo feeding L-Arginine for two generations. Issue 1 (June 2021) - Pakiding, W; Hakim, M R; Daryatmo,; Linggi, T R; Elis,
Abstract: In ovo feeding is a method to stimulate metabolic activity and nutrient availability in eggs during the incubation period with the aim of increasing embryo growth, hatching weight, development and growth after hatching. The nutritional composition, especially protein levels, in the ration given during the growth period is expected to optimize the growth and development of body components and improve reproductive characteristics of local chickens that has been treated in ovo L-arginine. The objective of the study was to determine the influence of different protein levels on body weight, body dimensions and reproductive characteristics of local chickens treated in-ovo feeding L-arginine for two generations (F2). Twelve 10-week-old female local chickens were used in this study. The chickens had received in ovo L-arginine treatment for two generations which was carried out on the 7 th day of the incubation period. The chickens were randomly assigned to 3 treatments, and each treatment was represented by 4 birds. The treatments were feed of different protein levels of 16, 18 and 20% with a metabolic energy of 3000 kcal/kg. The measurement of body weight and dimensions was carried out for 9 weeks and it continued until the chickens reached the reproductive phase for observation of age, body weight and egg weight at first laying. The results indicated that the application of different protein levels during the grower period did not significantly affect the increase in body weight and body dimensions. Regression analysis between body weight gain and body dimension gain showed that there was a significant relationship between chest circumference, tibial length and metatarsus length on body weight gain in native chickens showing chest circumference as the best predictor of body weight. The reproductive characteristics of age, body weight and egg weight at the first laying was not affected by the level of protein in the ration.